2013
DOI: 10.5414/cp201906
|View full text |Cite
|
Sign up to set email alerts
|

Application of population pharmacokinetic modeling to explore the impact of alternative roflumilast dosing regimens on tolerability

Abstract: Reduction of roflumilast dose in the first few weeks of therapy may be able to reduce the incidence of treatment-related AEs. Clearly, modeling provides only the basis for hypothesis generation, and must be supported with clinical evidence from carefully designed trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 0 publications
2
12
0
Order By: Relevance
“…In contrast to the discontinuation rates in these pivotal studies 3 , clinicians experience frequent adverse events in clinical practice. Alternative dosing strategies including dose escalation have not been clinically investigated.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…In contrast to the discontinuation rates in these pivotal studies 3 , clinicians experience frequent adverse events in clinical practice. Alternative dosing strategies including dose escalation have not been clinically investigated.…”
Section: Discussionmentioning
confidence: 96%
“…However, population pharmacokinetic/pharmacodynamics modeling 3 found that an alternative dose regimen, i.e., 250 µg once daily and the approved dose (500 µg) every other day regimens had minimal impact on efficacy and may reduce the risk of related adverse effects. Similarly, the frequencies of diarrhea, nausea, and headache were about two-fold lower in patients taking 250 µg roflumilast once daily than in those taking the approved 500 µg once daily regimen 3 . In the present study, of the 53 patients who increased to 500 µg roflumilast, 38 suffered no adverse effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These AEs, which reduced compliance to treatment, were confirmed by real-life studies 12,13 . Although the frequency and severity of AEs are dose-dependent 11 , a doseescalation regimen starting from 250 µg and then increased to 500 µg, did not significantly improve the adherence to the treatment 14,15 .…”
Section: Introductionmentioning
confidence: 94%